MSME Assistance Through Business Legality and Branding to Strengthen Penatarsewu Village's Local Economy - Hayati, Anis Khoirin; Febrianti , Sofi Intan; Silmi , Dewi Nurus (Indonesian Journal of Cultural and Community Development, 2025)
MSMEs are an important part of the Indonesian economy. In Penatarsewu Village, MSMEs excel with products such as smoked fish and herbal medicine. However, many MSMEs do not yet understand the importance of business legality, such as NIB and Halal Certificates, so that their access to a wider market is hampered. In response to this, the KKN-T Team 24 of the Muhammadiyah University of Sidoarjo provided assistance to MSMEs. They helped business actors understand the importance of legality, branding, and provided socialization. As a result, several MSMEs succeeded in obtaining NIB, assisting in registering Halal Certificates, and updating branding such as logos and packaging. In addition, they also created social media accounts and websites as a means of promotion. With this support, MSMEs are expected to grow more rapidly and support the village economy.